DESAIN DAN PEMBUATAN ULTRASONIC SPRAY DRYER UNTUK PRODUKSI GARAM HALUS SKALA LABORATORIUM - R.N. Akhsanu Takwim (INFO-TEKNIK, 2014)
One of the added values of the sea salt is to make it refined salt. The recent manufacture of refined salt , done with a lengthy process . It was started with evaporating of sea water, and then washing to remove impurities. Furthermore, the washed salt was dried again before refining process on the crusher and iodizing.  This study aimed to obtain an effective alternative technologies with a relatively low cost , so as to increase the added value for the local salt products.In this study will be designed and manufactured of an ultrasonic spray dryer prototype by integrate spray dryers technology with ultrasonic technology to product fined salt. Dimensions and capacity of each component is calculated to obtain a production capacity of 5 g/h . Salt product measured by a microscope and compared with conventional salt .As a result, heating air  flow of 12.235 m3 / h , air heater power of 320 watts , atomizer capacity of 250 ml / h and drying tube dimensions Ø400mm x 400mm at the top and cone with a height of 400mm at the bottom of the tube . Performance test results fined salt with 20μm to 25μm size . Keywords : Salt, ultrasonic, spray dryers, fineness.